2017
DOI: 10.2174/1573406412666161104121042
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking and Pharmacophore Modeling Studies of Fluorinated Benzamides as Potential CETP Inhibitors

Abstract: Ligand-based and structure-based drug design strategies confirm that hydrophobic interaction mediates ligand/protein complex formation and explains the activity of our verified molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…In order to explore the backbones of 8a–j and their attachments, we screened them against CETP inhibitors pharmacophore model . We found that 8a–j match the CETP inhibitors fingerprint (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to explore the backbones of 8a–j and their attachments, we screened them against CETP inhibitors pharmacophore model . We found that 8a–j match the CETP inhibitors fingerprint (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Utilizing a previously generated pharmacophore model by our group , and in order to get further details about the functionalities of the synthesized compounds responsible for activity, 8a–j were mapped against the adopted pharmacophore model of CETP inhibitors .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, our group designed and synthesized a range of different CETP inhibitors, including benzylidene-amino methanones (Abu , benzylamino methanones (Abu , N-(4-benzyloxyphenyl)-4-methyl-benzenesulfonamides (Abu Khalaf et al, 2012), N-(4-benzylamino-phenyl)toluene-4-sulfonic acid esters (Abu Khalaf et al, 2012), chlorobenzyl benzamides (Abu Khalaf et al, 2017a), fluorinated benzamides (Abu Khalaf et al, 2017b), and substituted benzyl benzamides (Abu Khalaf et al, 2017c). In an attempt to optimize our previously synthesized CETP inhibitors, compound A (% inhibition = 50% at 10 µM, Figure 1) was chosen as a lead (Abu Khalaf et al, 2017c).…”
Section: Introductionmentioning
confidence: 99%